2020
DOI: 10.1002/jobm.202000296
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antibacterial activity of synthesized ligand‐free CdS nanocrystals due to silver doping

Abstract: Recently, different nanocrystals have been reported to be the alternative, optimistic, and novel antimicrobial agent against the many antibiotic‐resistant bacteria. Here, ligand‐free CdS and Ag‐doped CdS (Ag/CdS) nanocrystals have been synthesized by chemical methods for the study of the antimicrobial activity on Escherichia coli and Staphylococcus aureus by Kirby–Bauer diffusion method to see the effect against Gram‐positive and Gram‐negative bacteria. These prepared nanocrystals have been characterized by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Thus, further studies must be conducted related to the compatibility of the biosynthesized nanostructures in our study for possible biomedical or industrial uses; however, several publications have proposed or demonstrated that CdS, Te, S, Au, Ag, and Cu NPs show application in diverse fields such as electronics and photonics (ex. solar cells and sensors), (bio)remediation of soil and water, agriculture, bioimaging, antimicrobial therapy and/or anticancer treatment [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, further studies must be conducted related to the compatibility of the biosynthesized nanostructures in our study for possible biomedical or industrial uses; however, several publications have proposed or demonstrated that CdS, Te, S, Au, Ag, and Cu NPs show application in diverse fields such as electronics and photonics (ex. solar cells and sensors), (bio)remediation of soil and water, agriculture, bioimaging, antimicrobial therapy and/or anticancer treatment [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Plos Onementioning
confidence: 99%
“…The major difference between the two types is the cell structures and the outer cell membranes. It is understand from the literature that the drug or any material depends upon mainly the nature of membranes of bacteria [83]. S. aureus and E. coli are the two bacterial strains used in the current investigation, the deadly bacteria, which induce various diseases.…”
Section: Antibacterial Studiesmentioning
confidence: 99%
“…Recent studies showed that transition metal sulfides with adjustable spectral characteristics and controlled morphology are very promising bactericidal agents capable of causing severe oxidative stress in bacteria under radiation [ 7 , 8 , 9 ]. At the same time, the development of methods for stabilizing nanoparticles is still relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to produce ROS has a dominant effect on antibacterial efficacy of CdS-based compounds. Antibacterial activity can rather be tuned by doping with metals or shape and size modifications [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%